Cholera—Modern Pandemic Disease of Ancient Lineage - Morris, J. Glenn (Centers for Disease Control and Prevention, 2011)
Cholera has affected humans for at least a millennium and persists as a major cause of illness and death worldwide, with recent epidemics in Zimbabwe (2008–2009) and Haiti (2010). Clinically, evidence exists of increasing severity of disease linked with emergence of atypical Vibrio cholerae organisms that have incorporated genetic material from classical biotype strains into an El Tor biotype background. A key element in transmission may be a recently recognized hyperinfectious phase, which persists for hours after passage in diarrheal feces. We propose a model of transmission in which environmental triggers (such as temperature) lead to increases in V. cholerae in environmental reservoirs, with spillover into human populations. However, once the microorganism is introduced into a human population, transmission occurs primary by “fast” transmission from person to person (taking advantage of the hyperinfectious state), without returning to the aquatic environment.